The reading of legal cases among law students - Ariffin, Adlina (2010)
One of the most essential skills for law students to be successful in their discipline is the ability to read legal cases. Christensen (2006) in her research entitled "Legal Reading and Success in Law School: An Empirical Study" shows that students who are able to read judicial opinions effectively and efficiently are more successful in their studies. However, the most common assumption is that students would have possessed this skill when they enroll in a law school. This attitudinal fallacy is referred to as “skills deployment assumption” (Stratman,1990). Thus, this paper describes a research which attempted to explore the common practices in the reading of legal cases among law students in a Malaysian public university. It emphasizes on the problems faced and the strategies employed by law students in carrying out the task. This study which adopted a case study design obtained the data through interview sessions with a few law students and lecturers. The results showed that more effective pedagogical approaches could be devised to assist students to overcome their problems in reading legal cases. Students were also found to have developed their own techniques in overcoming the difficulties in reading legal cases.